Incidence of Extravascular Perivertebral Artery Contrast Flow During Cervical Transforaminal Epidural Injections. Issue 9 (6th April 2020) - Levin, Joshua; Mohan, Manoj; Levi, David; Horn, Scott; Smuck, Matthew
Abstract: Background: During a cervical transforaminal epidural injection, injectate flows along the path of least resistance. Given the proximity of the vertebral artery to the intervertebral foramen, injected contrast may flow along the external wall of the artery. The incidence of this contrast flow pattern during cervical transforaminal epidural injections is unknown. Purpose: To determine the incidence of extravascular perivertebral artery contrast flow patterns during cervical transforaminal epidural injections. Study Design/Setting: Retrospective, observational, in vivo study. Patient Sample: Patients receiving cervical transforaminal epidural injections at a single outpatient spine clinic. Outcome Measures: The presence or absence of extravascular perivertebral artery contrast flow. Methods: The saved images from 100 consecutive patients were reviewed by two independent observers and classified with or without extravascular perivertebral artery contrast flow. The incidence was determined and kappa was used to examine inter-rater reliability. All disagreements were reviewed, and the final classification was determined by consensus. Results: The inter-rater reliability was moderate, with a kappa value of 0.69. The incidence of extravascular perivertebral artery contrast flow patterns was 49% by consensus. No statistically significant differences in incidence were present when comparing three different final needle tip positions. Conclusions: During a cervical transforaminal epidural injection, an extravascular perivertebral artery contrast flow pattern is frequently encountered. This includes flow along the exiting nerve and then around the vertebral artery, as suggested by this study. Although this contrast pattern does not represent an intravascular injection into the vertebral artery, practitioners should remain cautious to exclude intravascular needle placement before injecting medication.